Ecology of the (Brady)rhizobium symbiotic relationship with Fabaceae in the south-western Cape - Marumo, Moscow (Department of Biological Sciences, 2015)
The mediterranean ecosystems of the south-western Cape, South Africa occur mainly on nutrient-poor acid sands and less often on limestone and mixed limestone soil types which support a high species diversity of Fabaceae. This species richness and diversity is suggested to be a result of a high incidence of microsymbiont/host specificity among the fynbos Fabaceae (Cowling et al. 1990). This hypothesis by Cowling et al. (1990) has ignored other factors which may possibly play a major role in microsymbiont/host relationships in the Cape Floristic Region, such as soil conditions, and bacterial strain competition which may also influence patterns of nodulation in the region. Cowling et al.'s (1990) hypothesis was speculative and was without any experimental basis. In this thesis investigations were carried out to assess the applicability of this hypothesis to fynbos, while at the same time other factors that could affect the microsymbiont/host relationship in fynbos were investigated. In order to test Cowling et al.'s (1990) hypothesis, various complementary methods were used to assess the nodulation patterns of several indigenous fynbos species. Extracts from a range of soils differing in chemical and physical properties were used to inoculate test species, and their nodulation parameters observed. However, a second more specific approach was used to confirm the results of the previous study. This method involved cross-inoculation of indigenous test species used in the previous study with nodule homogenates prepared from other fynbos species originating from various sites within the Cape Floristic Region.